2018
DOI: 10.1080/21688370.2018.1463897
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of IBD associated diarrhea

Abstract: Inflammatory bowel diseases broadly categorized into Crohn's disease (CD) and ulcerative colitis (UC), are chronic inflammatory disorders of the gastrointestinal tract with increasing prevalence worldwide. The etiology of the disease is complex and involves a combination of genetic, environmental, immunological and gut microbial factors. Recurring and bloody diarrhea is the most prevalent and debilitating symptom in IBD. The pathogenesis of IBD-associated diarrhea is multifactorial and is essentially an outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
103
2
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 149 publications
2
103
2
3
Order By: Relevance
“…IBD often is associated with diarrhea [33,34] .The present study showed that diarrhea appeared in treated groups and the severity depended on the dose and method of administration. This potentially suggested the feasibility of antibiotic-induced IBD rat models.…”
Section: Comparison Of Pathological Inflammation Scoressupporting
confidence: 47%
“…IBD often is associated with diarrhea [33,34] .The present study showed that diarrhea appeared in treated groups and the severity depended on the dose and method of administration. This potentially suggested the feasibility of antibiotic-induced IBD rat models.…”
Section: Comparison Of Pathological Inflammation Scoressupporting
confidence: 47%
“…The expression of TJs in the gut varies according to the localization, such as villus vs. crypt and small bowel vs. colon 155 . The paracellular trafficking and intestinal epithelial permeability are essentially controlled by the TJs along with claudins, occludins, JAM, and tricellulin 16 . The extracellular domains of TJs connect to adjacent cells, thereby forming networks of linking strands.…”
Section: Tight Junction In Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Disturbances in luminal pH, in mucin synthesis and composition, mucus layer properties and secretory rate, and the luminal microbiome have also been described in patients with inflammatory bowel disease. [20][21][22][23][24] The first aim of the present study was an investigation into the consequences of lost Slc26a3 expression on the colonic mucus-bicarbonate "barrier," including the measurement of the colonic surface pH-microclimate and mucus output in vivo, and on the development of spontaneous intestinal inflammation. When we observed the striking goblet cell thecae depletion in the slc26a3 −/− colon, we also performed a microbiome analysis at the genera level, to obtain a first glimpse into the potential alterations of the colonic luminal microclimate to explain in part the reduced mucus content and development of mucosal inflammation.…”
Section: Introductionmentioning
confidence: 99%